Regulatory Stringency and COVID-19 Uncertainty Predict Consumer Animosity Toward Gojek Services Usage - Bilkis Aulia Luxfiati (Jurnal Riset Manajemen dan Bisnis, 2025)
Abstract. This study examines consumer animosity toward Gojek’s ride-hailing and delivery services in Indonesia during the COVID 19 pandemic. Rising case numbers, the national health emergency, and Large Scale Social Restrictions (PSBB) heightened perceptions of danger and uncertainty, reshaping consumer mobility and purchasing patterns. A conceptual model was developed linking perceived danger and service failures to negative word of mouth (NWOM), animosity toward the firm, and boycott intentions. The framework also highlights the role of digital platforms in accelerating NWOM during crisis conditions. Findings suggest that stricter government restrictions and higher perceived uncertainty intensify the pathway from animosity to NWOM and avoidance of Gojek services. This study expands consumer animosity research into domestic platform-based services and provides insights for policymakers and platform operators on reducing perceived risk, improving service reliability, and strengthening communication during public health crises.